2023
DOI: 10.32615/ps.2022.048
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in photosynthetic efficiency in soybean (Glycine max L.) varieties towards solar ultraviolet radiations

Abstract: Highlights• Intraspecific variations in photosynthetic performance were studied in soybean • UV-B exclusion upregulates chlorophyll, PSII efficiency, and photosynthesis • UV-B sensitivity is greater in soybean variety Hardee/PK-472 than NRC-7/PK-1029

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 99 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Soybean is an annual, self-pollinated, diploid (2n = 2x = 40), eudicot belonging to the family Fabaceae. Recently it has been reported that soybean crop growth and productivity were drastically reduced by the ambient and enhanced UV-B radiations (Kataria et al 2021, Baroniya et al 2023. Despite a rapid upsurge in production and coverage, soybean still suffers adversely on the productivity front.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Soybean is an annual, self-pollinated, diploid (2n = 2x = 40), eudicot belonging to the family Fabaceae. Recently it has been reported that soybean crop growth and productivity were drastically reduced by the ambient and enhanced UV-B radiations (Kataria et al 2021, Baroniya et al 2023. Despite a rapid upsurge in production and coverage, soybean still suffers adversely on the productivity front.…”
Section: Introductionmentioning
confidence: 99%
“…Kataria and Guruprasad (2012) experimented on four cultivars of wheat (Triticum aestivum L.) and noted maximum height and biomass accumulation increase at maturity under UV-B exclusion. According to Baroniya et al (2013Baroniya et al ( , 2023, UV-B exclusion improved stem height, leaf area, biomass, and yield parameters of different cultivars of soybean. It was also proposed that the ambient UV-B radiation resulted in the reduced growth, development, and yield of soybean plants due to the production of active oxygen species (Baroniya et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study dealing with UV-B radiation (Baroniya et al 2023), it has been reported that four soybean varieties (namely PK-1029, PK-472, NRC-7, and Hardee) performed differently and showed a degree of UV-B sensitivity. The significant increase in net photosynthesis was linked to increased stomatal conductance and lower intercellular concentration of CO 2 in UV-excluded plants.…”
mentioning
confidence: 99%